An atomistic simulation towards elucidation of operating temperature effect in CO2 swelling of polysulfone polymeric membranes - Lock, S.S.M. (Elsevier B.V., 2018)
A complementary study, which involves computational and in-house collected experimental work, has been employed to elucidate the swelling effect within polysulfone membranes by CO2 at varying operating temperatures. The simulation models have been constructed with accordance to collected experimental data. The experimental and simulated sorption isotherms of CO2 are in fairly good agreement with one another. Subsequently, the constructed molecular structures of unswollen and swollen polysulfone membrane at varying operating temperature has been analyzed to study the effect of CO2 in terms of physical characteristic, glass transition temperature, relaxation and free volume to determine whether the temperature or concentration parameters are more dominant in CO2 swelling. In addition, radial distribution function (RDF) between CO2 and varying groups within polysulfone has been evaluated to determine association reaction that invokes the dilation. RDF at various operating temperature has been employed to be incorporated within a series of thermodynamic equations in order to quantify the interaction of CO2 with polysulfone that constitutes to swelling. Â© 2018 Elsevier B.V.